1) Phân tích đa thức thành nhân tử bằng phương pháp dùng hằng đẳng thức:
a)x\(^4\)+y\(^2\)-2x\(^2\)y
b)(2a+b)\(^2\)-(2b+a)\(^2\)
c)(x\(^2\)+1)\(^2\)-4x\(^2\)
d)a\(^3\)+b\(^3\)+c\(^3\)-3abc
2)Chứng minh:
a)(7n-2)\(^2\)-(2n-7)\(^2\)\(⋮\)7 với n \(\in\)Z
b)n\(^3\)-n\(⋮\)6 với n\(\in\)Z
3) Tìm x pk
a)4x\(^3\)-36x=0
b)x\(^2\)-x+\(\frac{1}{4}\)=0
c)x\(^3\)-0,25x=0
d)x\(^2\)-10x=-25
1) Phân tích đa thức thành nhân tử
a)3x\(^5\)(x+1)-9x(x+1)
b)4x\(^2\)(x-2y)-20x(2y-x)
c)3x\(^2\)y\(^2\)(a-b+c)+2xy(b-a-c)
d)(a-b)\(^2\)-(b-a)
2)Tìm x, biết
a)x\(^3\)+4x=0
b)x(x-6)+10(6-x)=0
c)(x+2)\(^2\)=x+2
d)x(x+7)=4x+28